Carboplatin plus etoposide versus topotecan as second-line treatment for patients with sensitive relapsed small-cell lung cancer: an open-label, multicentre, randomised, phase 3 trial. Issue 9 (September 2020) - Baize, Nathalie; Monnet, Isabelle; Greillier, Laurent; Geier, Margaux; Lena, Hervé; Janicot, Henri; Vergnenegre, Alain; Crequit, Jacky; Lamy, Regine; Auliac, Jean-Bernard; Letreut, Jacques; Le Caer, Hervé; et al.
Summary: Background: Topotecan is currently the only drug approved in Europe in a second-line setting for the treatment of small-cell lung cancer. This study investigated whether the doublet of carboplatin plus etoposide was superior to topotecan as a second-line treatment in patients with sensitive relapsed small-cell lung cancer. Methods: In this open-label, randomised, phase 3 trial done in 38 hospitals in France, we enrolled patients with histologically or cytologically confirmed advanced stage IV or locally relapsed small-cell lung cancer, who responded to first-line platinum plus etoposide treatment, but who had disease relapse or progression at least 90 days after completion of first-line treatment. Eligible patients were aged 18 years or older and had an Eastern Cooperative Oncology Group performance status 0–2. Enrolled patients were randomly assigned (1:1) to receive combination carboplatin plus etoposide (six cycles of intravenous carboplatin [area under the curve 5 mg/mL per min] on day 1 plus intravenous etoposide [100 mg/m 2 from day 1 to day 3]) or oral topotecan (2·3 mg/m 2 from day 1 to day 5, for six cycles). Randomisation was done using the minimisation method with biased-coin balancing for ECOG performance status, response to the first-line chemotherapy, and treatment centre. The primary endpoint was progression-free survival, which was centrally reviewed and analysed in the intention-to-treat population. This trial is registered with ClinicalTrials.gov, NCT02738346 . Findings: Between July 18, 2013, and July 2, 2018, we enrolled and randomly assigned 164 patients (82 in each study group). One patient from each group withdrew consent, therefore 162 patients (81 in each group) were included in the intention-to-treat population. With a median follow-up of 22·7 months (IQR 20·0−37·3), median progression-free survival was significantly longer in the combination chemotherapy group than in the topotecan group (4·7 months, 90% CI 3·9–5·5 vs 2·7 months, 2·3–3·2; stratified hazard ratio 0·57, 90% CI 0·41–0·73; p=0·0041). The most frequent grade 3–4 adverse events were neutropenia (18 [22%] of 81 patients in the topotecan group vs 11 [14%] of 81 patients in the combination chemotherapy group), thrombocytopenia (29 [36%] vs 25 [31%]), anaemia (17 [21%] vs 20 [25%]), febrile neutropenia (nine [11%] vs five [6%]), and asthenia (eight [10%] vs seven [9%]). Two treatment-related deaths occurred in the topotecan group (both were febrile neutropenia with sepsis) and no treatment-related deaths occurred in the combination group. Interpretation: Our results suggest that carboplatin plus etoposide rechallenge can be considered as a reasonable second-line chemotherapy option for patients with sensitive relapsed small-cell lung cancer. Funding: Amgen and the French Lung Cancer Group (Groupe Français de Pneumo-Cancérologie).